Perancangan Model Pengukuran Jarak Menggunakan Computer-Aided pada Kontrol Kualitas Ultrasonografi - Fallo, Frida; Adi, Kusworo; Suryono, Suryono (BERKALA FISIKA, 2014)
This research purposes are to do some quality tests through a distance measuring calculation using computer-aided system in a USG image projection and to analyze the distance measuring. In concerning with the design and its implementation, this research used digital tabulation method of image projection to compute and to analyze the distance measuring. The image value was established by variation of attenuation, TGC, and depth. Image tabulation was processed with ROI establishing and the cropping method. In depth variation, the average real distance of USG image resolution is 1 cm, the average value of vertical distance accuration of the image is 0.9747, thus the error value of the vertical distance accuration is 0.0253 cm or 0.253 mm or 0.253 % from the real distance andÂ the average value of the horizontal distance accuration of the image is 0.998 cm thus the error value of the horizontal distance accuration is 2x10-3 cm or 0.02 mm or 0.02 % from the real distance. For the variation of attenuation, the average value of vertical distance accuration of the image is 0.967 thus the error value of the vertical distance is 0.033 cm 0.33 mm or 0.33 %, andÂ the average value of the horizontal distance accuration of the image is 0.986 cm thus the error value of the horizontal distance is 0.014 cm 0r 0.14 mm or 0.14 %. Thus the error value for the vertical distance accuration is 0.031 cm or 0.31 mm or 0.31 % from the real distance. The result of the all tested components showed that the tested USG machine fullfiled the qualification of The American Association of Physicists in Medicine (AAPM) criteria. Keywords : USG, Quality Control, Distance Accuration, Computer-Aided